1977
DOI: 10.1113/jphysiol.1977.sp011690
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the mechanosensory innervation of the salmander skin.

Abstract: SUMMARY1. We have investigated by physiological means the characteristics and organization of the mechanoreceptors in the skin of the salamander hind limb. A controlled mechanical stimulator with a tip diameter of a few microns was used to activate single mechanoreceptors, and afferent impulses were recorded from whole spinal nerves.2. The mechanoreceptors of the skin are rapidly adapting. When random spots on the skin were tested, the stimulus strength needed to evoke an impulse varied from one location to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…In the 6-day animal, however, changes in the distribution of the critical stimulus were clearly apparent; there were fewer low-threshold spots, many more in the higher stimulus range (thereby completely changing the shape of the histogram from its usual skewed distribution), and a significant increase in non-responsive spots. By day 7 about 95 % of the touch receptor population was not detectable with the largest stimuli we were able to apply with our mechanical stimulator (Cooper & Diamond, 1977).…”
Section: Nerve Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the 6-day animal, however, changes in the distribution of the critical stimulus were clearly apparent; there were fewer low-threshold spots, many more in the higher stimulus range (thereby completely changing the shape of the histogram from its usual skewed distribution), and a significant increase in non-responsive spots. By day 7 about 95 % of the touch receptor population was not detectable with the largest stimuli we were able to apply with our mechanical stimulator (Cooper & Diamond, 1977).…”
Section: Nerve Sectionmentioning
confidence: 99%
“…In the preceding paper (Cooper & Diamond, 1977) we analysed the distributions of sensitivities of these mechanosensory endings to obtain a measure of their density in the skin. In the present report we use this information to examine the effects of colchicine on the mechanoreceptor function and distribution, both of the treated nerves and of the adjacent nerves supplying the skin of the salamander hind limb.…”
Section: Control Of Mechanoreceptor Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…But it introduces a new one: when competition modifies the competitive capacity, the fittest axon becomes so strong that it eliminates all the others. This competitive exclusion appears indeed to occur in certain situations, such as the elimination of polyneuronal innervation of muscle fibers during development [49,50] or the mosaic organization of skin innervation by rapidly adapting terminals in salamanders [51], but not in others such as the overlapping arrangement of axonal fields in the skin of frogs [52]. Moreover, this earlier model predicted that competitive exclusion would still occur even with very high levels of trophic factor production, implying that the total number of axons innervating a region would not be increased, but experiments involving the overexpression of neurotrophins in the skin have shown that innervation density does increase in the skin in general [46], and in touch domes in particular [19].…”
Section: Modeling Axonal Competition As a Determinant Of Neuronal Deathmentioning
confidence: 99%